Hallazgos ultrasonográficos según clasificación tirads en adultos con sospecha de patología tiroidea. Hospital Regional Docente de Trujillo - Piccone Vargas, Francis (2014)
Determine ultrasound findings according to TIRADS classification in adults with suspected thyroid disease. Materials and Methods: To do medical records of 70 adult patients was reviewed with suspected thyroid disease treated in outpatient clinics (Otolaryngology and Internal Medicine) of Trujillo Regional Teaching Hospital between January 2012 to December 2012. Results: The distribution of the ultrasound findings according to TIRADS classification in adults with suspected thyroid disease was: TIRADS 1 26 (37.14%) (CI: 95%: 25.11 to 49.18%), TIRADS 2 19 (27.14%) (CI 95 %: 16.01% - 38.28%); TIRADS 3 10 (14.29%) (CI 95%: 5.37% - 23.20%), TIRADS 4 13 (18.57%) (CI 95%: 8.75% - 28.40%) and TIRADS 5 02 (2.86%) (CI 95 %: 0.35% -9.94%). In all categories TIRADS female sex is the predominance in TIRADS 1 category in 84.6% of patients and 89.5% in TIRADS 2. The age group 40 to 65 was the most frequent. Conclusions: In the present study we found that TIRADS categories 1 and 2, female sex and age group of 40-65 years were the most frequent